2016
DOI: 10.1093/jcr/ucw080
|View full text |Cite
|
Sign up to set email alerts
|

Costly Curves: How Human-Like Shapes Can Increase Spending

Abstract: Can exposure to body shapes affect spending preferences? Because Western society associates thinness with economic value, we argue that a shape resembling thin human body types activates concepts related to positive financial outcomes, such as responsibility and hard work. The results of five experiments show that exposure to thin, human-like shapes influences consumer self-efficacy judgments and spending outcomes, depending on the perceiver’s weight. In line with social comparison, we demonstrate that seeing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 82 publications
2
25
0
Order By: Relevance
“…In line with prior empirical studies reporting negative correlations between BMI and self-efficacy (e.g., Ovaskainen et al 2015; Sacco et al 2007) and following insights from studies on goal-oriented health behaviors (Romero and Craig 2017), we expect that BMI has a negative moderating influence on the effect of STT use on advice compliance. 1 For instance, higher BMI ratios indicate a lower ability to appreciate the long-term benefits of one’s choices such as the decision to comply with expert recommendations (Ikeda, Kang, and Ohtake 2010).…”
Section: Hypotheses Developmentsupporting
confidence: 78%
See 1 more Smart Citation
“…In line with prior empirical studies reporting negative correlations between BMI and self-efficacy (e.g., Ovaskainen et al 2015; Sacco et al 2007) and following insights from studies on goal-oriented health behaviors (Romero and Craig 2017), we expect that BMI has a negative moderating influence on the effect of STT use on advice compliance. 1 For instance, higher BMI ratios indicate a lower ability to appreciate the long-term benefits of one’s choices such as the decision to comply with expert recommendations (Ikeda, Kang, and Ohtake 2010).…”
Section: Hypotheses Developmentsupporting
confidence: 78%
“…Finally, our finding that BMI can serve as a physiological proxy for self-efficacy extends knowledge on consumer differences that affect outcomes of technology-based services. Taken together, we contribute to studies that seek to investigate the role of physiological traits in consumer behavior and decision-making in general (e.g., Aspara and van den Bergh 2014) and the one of BMI in particular (e.g., Romero and Craig 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, to further generalize the results, these studies use different robots: Studies 1a and 1b use one humanoid robot, and Study 1c uses a different humanoid robot (see Figure 1, Panels A and B). In all our studies, we control for gender and age (Briers and Laporte 2013; McCrory et al 1999; Romero and Craig 2017), factors that influence compensatory behaviors; we also control for the perceived novelty of the service experience to rule out mere novelty effects related to robots (Roehrich 2004). 1 As Web Appendix A details, the set of control variables used in our research is consistent with prior literature.…”
Section: Study 1: Do Hsrs Trigger Compensatory Consumer Behavior?mentioning
confidence: 99%
“…Participants completed what appeared to be a different study about product choices related to the $2.00 they were given and the water they saw upon entering the lab. Following Romero and Craig’s (2017) procedure, participants were shown a photo of a bottle of Fiji water for $1.50 and a bottle of generic water for $.95 and were asked to select one of the bottles to purchase using the $2.00 they received. After indicating which bottle of water they wanted to purchase, participants indicated their age and gender, their level of thirst (Crolic and Janiszewski 2016), and whether they had brought a beverage with them to the lab.…”
Section: Study 1: Do Hsrs Trigger Compensatory Consumer Behavior?mentioning
confidence: 99%
“…Self-efficacy is defined as a person’s perception of his or her capability to achieve a certain level or type of performance (Gist 1987). Prior research has differentiated general self-efficacy and domain-specific self-efficacy, showing that both affect outcomes in domains such as financial decisions (Romero and Craig 2017) and academic performance (Bandura 1993). In general, studies have shown that domain-specific self-efficacy (e.g., financial self-efficacy) has similar effects as generalized self-efficacy (Bandura 1993).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%